Using Task Analysis in Physical Education Routines for Elementary Students with Autism Spectrum Disorder. - Sulaimani, Mona F.; Alshegebi, Yahya D.; Tufekcioglu, Ertan (JOPERD: The Journal of Physical Education, Recreation & Dance)
Effective inclusion in physical education for students with autism spectrum disorder requires educators to establish a supportive and accessible learning environment. This article describes how the experiences of these students can be enhanced by using task analyses to break down complex skills and routines into smaller, manageable steps to teach them sequentially.